2018
DOI: 10.3390/electronics8010008
|View full text |Cite
|
Sign up to set email alerts
|

Partial Isolation Type Saddle-FinFET(Pi-FinFET) for Sub-30 nm DRAM Cell Transistors

Abstract: In this paper, we proposed a novel saddle type FinFET (S-FinFET) to effectively solve problems occurring under the capacitor node of a dynamic random-access memory (DRAM) cell and showed how its structure was superior to conventional S-FinFETs in terms of short channel effect (SCE), subthreshold slope (SS), and gate-induced drain leakage (GIDL). The proposed FinFET exhibited four times lower I off than modified S-FinFET, called RFinFET, with more improved drain-induced barrier lowering (DIBL) characteristics, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…This is because the deep penetration of the buried insulator limits the lateral PDW in the narrow silicon layer between the gate and drain regions and this lateral PDW becomes narrow. Our previous study confirmed that if the ratio of L in to L g is 50% or below, the I off increases [14]. However, high electric field due to the narrow PDW is formed only in the upper side of the buried insulator and the rest of the region has a smaller electric field than Pi-FinFETs that have 20nm L in (66.7%).…”
Section: Ioff Fluctuationsupporting
confidence: 66%
See 2 more Smart Citations
“…This is because the deep penetration of the buried insulator limits the lateral PDW in the narrow silicon layer between the gate and drain regions and this lateral PDW becomes narrow. Our previous study confirmed that if the ratio of L in to L g is 50% or below, the I off increases [14]. However, high electric field due to the narrow PDW is formed only in the upper side of the buried insulator and the rest of the region has a smaller electric field than Pi-FinFETs that have 20nm L in (66.7%).…”
Section: Ioff Fluctuationsupporting
confidence: 66%
“…The buried insulator parameters, i.e., silicon film thickness, buried insulator thickness, and L in were set as 20, 100 and 20 nm, respectively. These parameters were chosen to minimize leakage current while maintaining a high on-current as possible [14]. An n+ poly gate with a gate work function of 4.6 eV was applied.…”
Section: B Device Structurementioning
confidence: 99%
See 1 more Smart Citation
“…New concepts of data storage and memory devices are another focus of this issue. A partial isolation type saddle-FinFET has been proposed for sub-30 nm DRAM applications [9]. A new method for neural networks based on resistive switches has been proposed for pattern storage and recognition [10].…”
Section: The Current Research Trendsmentioning
confidence: 99%
“…The structures presented in this paper are fabricated using a 3D device simulation (sentaurus TCAD). These device structures use a Gaussian distribution of the doping concentration in order to provide a reliable doping profile [25][26][27].…”
Section: Introductionmentioning
confidence: 99%